1989
DOI: 10.3109/00016348909015754
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Developing Urinary Stress-Incontinence After Vaginal Repair in Continent Women :A Clinical and Urodynamic Follow-Up Study

Abstract: A study was performed to find out how often continent women develop urinary stress-incontinence after a Manchester operation for genito-urinary prolapse, and to ascertain whether factors in the selection of patients, or steps in the surgical procedure are responsible for producing stress-incontinence postoperatively. Seventy-three of 102 consecutive patients were continent before operation. Sixteen of the 73 women (22%) became stress incontinent. Advanced age increased the risk of developing urinary stress-inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 9 publications
5
51
2
1
Order By: Relevance
“…The literature would seem to indicate that somewhere between 30% and 80% of women with advanced anterior vaginal wall prolapse are at risk for the development of stress incontinence if adequate urethral support or obstruction is not achieved at the time of surgery. Recent data have noted that this is markedly overestimated [1][2][3]. My experience would agree with this statement.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The literature would seem to indicate that somewhere between 30% and 80% of women with advanced anterior vaginal wall prolapse are at risk for the development of stress incontinence if adequate urethral support or obstruction is not achieved at the time of surgery. Recent data have noted that this is markedly overestimated [1][2][3]. My experience would agree with this statement.…”
supporting
confidence: 67%
“…The first was a Scandinavian report whose authors made no effort to improve urethral support. The study found that 22% of women had de novo stress incontinence after the prolapse repair [2]. A second study by Columbo et al [3] noted that there was no difference in the development of stress incontinence if a posterior pubourethral ligament repair at the level of the bladder neck was performed in conjunction with the cystopexy, rather than a cystopexy alone, in patients with advanced anterior vaginal prolapse who did not have any incontinence with reduction maneuvers at the time of preoperative testing.…”
mentioning
confidence: 95%
“…1,2 Continent women can also develop SUI after surgery. [3][4][5] The risk is assumed to be highest (up to 80%) in the 20-30% of continent women with occult SUI, and is believed to be associated with kinking or compression of the urethra by the prolapse. [3][4][5][6][7] The combination of prolapse surgery with an anti-incontinence procedure to treat or prevent SUI is frequently considered in three patient groups: (1) women with coexisting SUI; (2) women asymptomatic for SUI; and (3) women asymptomatic for SUI with occult SUI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, postoperative stress urinary incontinence (de novo stress urinary incontinence) has been noted in 10 to 30% of women following prolapse repair (Bump et al, 1996;Hung et al, 2004;Reena et al, 2007). Other reports estimate that 11 to 65% of continent patients with pelvic organ prolapse develop de novo stress urinary incontinence following pelvic reconstructive procedures performed during prophylactic anti-incontinence surgery (Borstad E and Rud T, 1989;Ellerkmann et al, 2001;Gutman et al, 2008).…”
Section: Prevalence Of Pelvic Organ Prolapse Associated Stress Urinarmentioning
confidence: 99%